‘Vulnerability’, an Interesting Concept for Public Health: The Case of Older Persons - Luna, Florencia (2014)
Traditional accounts of vulnerability tend to label entire populations as vulnerable. This approach is of limited utility. Instead, this article utilizes a layered approach to vulnerability, identifying multiple vulnerabilities that older people experience. It focuses on distinguishing the different layers of vulnerability that may be experienced by the elderly in middle-income countries of Latin America. In doing so, I show how the layered approach to vulnerability functions, and demonstrate why it is more interesting and useful than the traditional approach. The article achieves three things. First, it unwraps the different potential layers of vulnerability that develop in old age and the multidimensionality aspects of aging. Second, it reestablishes the usefulness of the concept of vulnerability and explains its functioning. Finally, it shows how different policies can be designed in order to address each vulnerability layer. The layered account promotes a multifaceted approach to public policy analyses and design. In this sense, the layered concept of vulnerability is an appealing concept to consider in public health ethics.